1994
DOI: 10.1093/carcin/15.10.2319
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genotoxicity of 2,3'-O-cyclocytidine, β-xylocytidine and 1-β-D-arabinofuranosylcytosine in human tumor cell lines

Abstract: We have investigated the genotoxicity of two 3'-derivatives of cytidine, 2,3'-O-cyclocytidine (3'-cycloC) and beta-xylocytidine (xyloC), in human leukemia and solid tumor cell lines. Both derivatives were found to be cytotoxic at micromolar concentrations. For example, in the alveolar tumor cell line A549 which was included in all experiments as a reference, drug concentrations required to induce 50% inhibition of cell growth (D50 values) equalled 55 microM for 3'-cycloC and 80 microM for xyloC. Compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…To achieve this goal, repair sites were selectively converted to chromosome breaks by using Ara-C, a competitive inhibitor of the DNA polymerases (Mirzayans et al, 1994). Previous studies showed that Ara-C blocks not only de novo semiconservative DNA synthesis by incorporating itself to nascent strands, but also DNA repair of lesions induced by UV light and other genotoxic agents (reviewed in Mirzayans et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this goal, repair sites were selectively converted to chromosome breaks by using Ara-C, a competitive inhibitor of the DNA polymerases (Mirzayans et al, 1994). Previous studies showed that Ara-C blocks not only de novo semiconservative DNA synthesis by incorporating itself to nascent strands, but also DNA repair of lesions induced by UV light and other genotoxic agents (reviewed in Mirzayans et al, 1994).…”
Section: Discussionmentioning
confidence: 99%